ANALYSIS OF LEARNING METHODS IN INCREASING STUDENTS’ LEARNING MOTIVATION - Achruh, Andi; Ahsan, Amrul Aysar; Rusydi Rasyid, Muhammad; Annisa, A. Alsyab (AULADUNA: Jurnal Pendidikan Dasar Islam, 2023)
Abstract This study aimed to identify effective learning strategies for enhancing student motivation in Islamic Education (PAI) subjects during distance learning caused by the Covid-19 pandemic. The research employed a qualitative approach in the form of field research using data collection through observation, interviews, and documentation. The study was conducted at SDIT Wihdatul Ummah Makassar. Data sources in this research were Islamic Education teachers, homeroom teachers, students, and their parents. The results indicated that the implementation of lectures, question and answer, assignments, class discussions, storytelling, assignments, and giving rewards and punishments enhanced students’ learning motivation. Supporting and inhibiting factors to increase students’ learning motivation in Islamic Education subjects at SDIT Wihdatul Ummah Makassar during the Covid-19 pandemic were diverse. Internally, they included adequate facilities, distance limitations, enthusiasm for learning, as well as the students’ behaviour and cheerfulness. Externally, several factors contributed to effective teaching, including the teacher’s proficiency in teaching materials, their commitment to teaching with creativity and diligence, the assistance and support provided by parents at home, the teacher’s use of innovative learning techniques, and the involvement and support of homeroom teachers.